Legal Innovations and Barriers in Climate Change Litigation: A Global Narrative Review - Hermansyah (Legalis : Journal of Law Review, 2025)
This narrative review explores the evolving landscape of climate change litigation and its intersection with environmental justice. The study aims to analyze legal innovations, structural barriers, and community participation in global climate litigation, with a particular focus on the integration of human rights frameworks. Literature was retrieved from Scopus, Web of Science, Google Scholar, JSTOR, and HeinOnline using targeted keywords and Boolean combinations. Inclusion criteria focused on peer-reviewed studies and legal analyses discussing litigation, human rights, and environmental justice.Findings reveal a significant rise in legal innovations, including the judicial recognition of environmental rights and the application of intergenerational equity. Human rights-based litigation has influenced courts to mandate stronger climate action, especially in Europe and Latin America. However, substantial structural and institutional barriers remain, such as procedural limitations and weak institutional capacity, particularly in developing countries. Civic engagement and community-generated evidence emerged as key drivers in legitimizing claims and shaping litigation outcomes. Comparative analysis illustrates that while developed nations benefit from robust legal systems, emerging innovations in Africa and Latin America also contribute to transformative environmental governance. The study concludes that climate litigation serves as a critical tool for enforcing environmental accountability. It calls for systemic reforms to strengthen access to justice, integrate legal outcomes into policymaking, and expand participatory legal frameworks. Further research should assess the durability of legal precedents and the broader socio-political impacts of litigation.